Retrograde placement of a novel 3.5 mm titanium interlocking nail for supracondylar and diaphyseal femoral fractures in cats - Scotti, S.; Klein, A.; Pink, J.; Hidalgo, A.; Moissonnier, P.; Fayolle, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Twenty-four simple or comminuted supracondylar and diaphyseal femoral fractures in cats, which had been treated by retrograde insertion of a new 3.5 mm titanium interlocking nail (IN) from the intercondylar notch, were evaluated between June 2000 and October 2004 at the Ecole Nationale Vétérinaire d'Alfort. Patient data (species, breed, weight, and age), fracture characteristics, details of the surgery, post-operative complications and radiographic follow-up were recorded. The mean body weight was 3.75 kg and the cats ranged in age between four and 66 months (mean 29 months). The IN had a diameter of 3.5 mm and a length of 100, 109 or 119 mm, and were all fixed in a static position (two screws in seven cats, three screws in 10 cats and four screws in seven cats). Cerclage wires were used in seven cats and an autogenous bone graft was used in two cats. Screw or nail breakage were not recorded. Nineteen fractures healed without any complications, three cats died during the post-operative period from unknown causes, and two cats showed delayed bone healing. Twenty cats were considered to have an excellent limb function at one month. One cat with a sciatic injury was non-weight bearing for several months. Radiographic signs of degenerative joint disease of the stifle joint were not observed except in the cat with the sciatic nerve injury. The results of this study suggest that this new 3.5 mm titanium IN can be introduced from the intercondylar notch and be used in static fixation mode to stabilize supracondylar and diaphyseal femoral fractures in cats.
Keywords: Interlocking nail; supracondylar; femoral; intercondylar notch; titanium